Izobraževanje kot pomemben dejavnik pri preprečevanju amputacij spodnjega uda zaradi žilne problematike - Petkovšek Gregorin, Romana (Rehabilitacija (Ljubljana), 2016)
Background: Peripheral arterial disease has been identified as a key cause of amputations of the lower limb. The patients can widen their knowledge about the care of their feet through education. With knowledge and consistent care for the limb at risk, they can avoid potential problems that lead to limb amputation. The aim of our study was to assess whether there is a difference in knowledge about the care of the residual limb between patients with different causes of amputation and whether there is a difference in knowledge before and after the education.
Keywords: amputacija; Amputation; education; izobraževanje; knowledge; nursing; periferna arterijska bolezen; Peripheral Arterial Disease; prevention and control; Rehabilitation Nursing; zdravstvena nega; znanje